2019
DOI: 10.1177/0003489419853304
|View full text |Cite
|
Sign up to set email alerts
|

Revision Stapes Surgery in a Tertiary Referral Center: Surgical and Audiometric Outcomes

Abstract: Objectives: To evaluate pure-tone audiometric results in otosclerosis patients undergoing revision stapes surgery following previous middle ear interventions. Methods: A retrospective cohort study was performed in a tertiary referral center. Consecutive otosclerosis patients who underwent revision stapes surgeries, following previous middle ear interventions, for persistent conductive hearing loss, recurrent conductive hearing loss, or vertigo and had available postoperative pure-tone audiometry were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
2
14
0
1
Order By: Relevance
“…These results might suggest that, independently from their blood concentration, female hormones might impact on the ligament elasticity improving the ossicular chain movements [ 21 , 22 ]. Furthermore, we found that all the patients that preserved good bone conduction thresholds successfully recovered their auditory function, thus confirming the previous studies about the efficacy of surgery in these type of patients [ 15 , 17 , 18 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…These results might suggest that, independently from their blood concentration, female hormones might impact on the ligament elasticity improving the ossicular chain movements [ 21 , 22 ]. Furthermore, we found that all the patients that preserved good bone conduction thresholds successfully recovered their auditory function, thus confirming the previous studies about the efficacy of surgery in these type of patients [ 15 , 17 , 18 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…The primary causes of failure in this study—including prosthesis displacement, reparative granuloma, lateral chain fixation, extensive fibrotic bands, and a persistently intact footplate—have all been indicated in prior studies, although their relative frequencies vary. 3,4 Most failures in this study were due to prosthesis displacement with or without incus erosion. Cases of prosthesis displacement without incus erosion are likely attributable to technical errors, such as a short prosthesis or inadequate stapedotomy, while cases with incus erosion are more likely to result from ischemic changes to the incus due to overcrimping or tenuous perfusion.…”
Section: Discussionmentioning
confidence: 83%
“…Revision stapes surgery is less likely to succeed than primary surgery, with rates of ABG closure to \10 dB HL varying in recent reports from 40% to 70%. 4,[9][10][11] Our cohort fit into this range, with 66% of patients achieving an ABG \10 dB. In comparison, this degree of hearing improvement is achieved in up to 90% of primary surgery procedures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…La cirugía de revisión de otoesclerosis ha sido uno de los criterios de exclusión en la selección de la muestra, y los porcentajes de éxito obtenidos se suelen analizar diferenciándolos de los de la cirugía primaria. Es por ello que sería interesante realizar una evaluación en próximos estudios (8,12,13).…”
Section: Discussionunclassified